Religious Moderation In An Islamic Perspective: Literature Review And Recent Research Developments - Azis, Saipul; Samad, Duski (Moderatio: Jurnal Moderasi Beragama, 2024)
In recent years, religious moderation has become the focus of intense debate, as extremism and misperceptions of the religion emerge This article discusses recent developments in religious moderation with a focus on efforts to maintain a balance between religious values and the times.  This research combines approaches (quantitative and qualitative) in the form of bibliometric analysis and literature review. The results of the bibliometric analysis are dominated by FM Manshur and H Husni's research in promoting religious moderation through literature-based learning. Understanding religious moderation and developing a multicultural-based curriculum are the focus of research that gets a significant number of citations. The results of the literature review discuss the concepts and principles of religious moderation, as well as the role of religious moderation in everyday life. Religious moderation is needed at this time, with the existence of religious moderation can be a middle way to resolve conflicts and realise the mission of Islam rahmatan lil alamin. The role of religious leaders, education, and the role of social movements can build an inclusive and tolerant society. Recent reforms in religious moderation aim to maintain a balance between religious values and the demands of the times, by adopting Islamic principles with growing social problems. Thus, religious moderation is the key to building a harmonious and just society